CBCT Verification of SRT for Patients With Brain Metastases - Papp, Judit; Simon, Mihály; Csiki, Emese; Kovács, Árpád (Frontiers in Oncology, 2022)
Background: The aim of our work is to demonstrate the role of image guidance and volumetric imaging in stereotactic radiotherapy (SRT) of brain metastases. Methods: Between 2018 and 2020, 106 patients underwent intracranial stereotactic radiotherapy. 10 patients with metastatic brain tumors treated with SRT were randomly selected and included in our study model. Patients were scanned pre- and post-treatment with cone beam CT. Total of 100 verifications of 50 stereotaxic treatments were performed and analyzed. Results: Population mean X, Y, Z values were -0.13 cm, -0.04 cm, -0.03 cm, respectively, rotation values 0.81°, 0.51°, 0.46°, respectively. Systematic error components for translational displacements pre corrections were as follows: 0.14 cm for X, 0.13 cm for Y and 0.1 cm for Z. Systematic error components of the post-treatment HR 3D CBCTs were as follows: 0.01 cm for X, 0.06 cm for Y and 0.04 cm for Z. Conclusions: Population mean values close to 0 confirmed that there is no systematic variation in our system and the accuracy of our equipment and tools is reliable. HR 3D CBCT scans performed pre SRTs further refine patient and target volume setting, support medical decision making and eliminate the possibility of gross error.